2014
DOI: 10.1155/2014/458263
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antiprotozoal Activity of the Chloroform Extract from Carica papaya Seeds against Amastigote Stage of Trypanosoma cruzi during Indeterminate and Chronic Phase of Infection

Abstract: In order to evaluate the antiprotozoal activity of the chloroform extract of Carica papaya seeds during the subacute and chronic phase of infection of Trypanosoma cruzi, doses of 50 and 75 mg/kg were evaluated during the subacute phase, including a mixture of their main components (oleic, palmitic, and stearic acids). Subsequently, doses of 50 and 75 mg/kg in mice during the chronic phase of infection (100 dpi) were also evaluated. It was found that chloroform extract was able to reduce the amastigote nests nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…This aspect could partially explain the rarity of studies investigating the chronic phase of T. cruzi (Jiménez-Coello et al . 2014) and T. brucei (Nasimolo et al . 2014) infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect could partially explain the rarity of studies investigating the chronic phase of T. cruzi (Jiménez-Coello et al . 2014) and T. brucei (Nasimolo et al . 2014) infections.…”
Section: Discussionmentioning
confidence: 99%
“…Since parasitaemia can drop to undetectable levels in chronic stages (Marin-Neto et al 2007;Bern, 2015), it is difficult to accurately determine if the beneficial outcomes are determined by a direct parasitic control of the products tested or by a secondary effect of the product on the metabolism and structure of the target organs in both diseases. This aspect could partially explain the rarity of studies investigating the chronic phase of T. cruzi (Jiménez-Coello et al 2014) and T. brucei (Nasimolo et al 2014) infections.…”
Section: Discussionmentioning
confidence: 99%
“… [ 129 ] Carica papaya Crude seed extracts Extracts were able to reduce parasitemia, but not the cardiac amastigotes nests of infected mice. [ 127 ] Delphinium staphisagria Flavonoids from aerial parts Flavonoids were active against T. cruzi in vitro and in infected mice. [ 124 ] Artemisia annua artemisinin (sesquiterpene lactone) Artemisinin presented in vitro activity and inhibited calcium-dependent ATPase activity in T. cruzi membranes.…”
Section: Natural Productsmentioning
confidence: 99%
“…Natural products isolated from different botanical sources exhibited activity against T. cruzi (see Table 2). [120][121][122][123][124][125][126][127][128][129][130][131][132] Several approaches have been developed focusing on identification and isolation of plantbased products with anti-T. cruzi activity 133,134 (Table 2). In this sense, extracts from different plants as Salvia, Valeriana, Hypericum, Silybum, Arnica, and Curcuma showed activity against T. cruzi.…”
Section: Natural Productsmentioning
confidence: 99%
“…Some data also indicated that it has antiprotozoal activity. Therefore, Jimenez-Coello et al [60] evaluated the effects of extracts and a mixture of the main components of C. papaya against T. cruzi amastigotes during subacute phase and chronic disease. Results showed that chloroformic extract was able to reduce the number of amastigotes (55.5 and 69.7%) in cardiac tissue of infected mice during the subacute phase at a concentration of 50 and 75 mg/kg, respectively.…”
Section: Relevant Studies About Mexican Plant With Activity Against Tmentioning
confidence: 99%